Follicular phase of menstrual cycle is related to higher tendency to suffer from severe injuries among elite female futsal players - Lago-Fuentes, C.; Padrón-Cabo, A.; Fernández-Villarino, M.; Mecías-Calvo, M.; Muñoz-Pérez, I.; García-Pinillos, F.; Rey, E. (Physical Therapy in Sport, 2021)
Objective To describe the injury incidence according to each phase of menstrual cycle (MC) in professional futsal players along two consecutive season and, secondly, to compare the injury incidence and frequency between different phases of the MC.